PEMBERDAYAAN PEREMPUAN MELALUI DANA DESA DI DESA TAMMEJARRA KABUPATEN MAMUJU SULAWESI BARAT - Sadriani Ilyas; Mario S.M (PREDESTINATION: Journal of Society and Culture, 2020)
This study  aims  to  find  out 1)  the factors  driving  women’s participation in the empeworment process trought the village fund, 2) the forms of women’s participation in the empowerment process trought village fund in Tammejarra Village, Mamuju Regency West Sulawesi. This type of research is descriptive qualitative research. The number of informants is 12 peopole. The selection of informants in this study  uses o purposive sampling method with informant criteria: a) Women who actively participate in organizations or groups in Tammejarra   Village,   b)   Women   who   actively   participate   in   Village   meetings   and deliberation, c) Age 25-50 years old, d) Merried women. Data collection techniques used are observation, interview, and documentation. Data analysis techniques use data reduction data presentation, as well as drawing conclusions and verification. The data validation technique uses persistence of observation and triangulation. The results of this study indicate that: 1) The factors driving women’s participation in the  empowerment  proses  trought  village  funds include  women’s awareness  to  build  the village, the desire to learn, abilities that include physical abalities in the form of skills, access to women’s involvement and, support from family. There any factors for women’s participation include double workload, lack of self-confidence and lack of business fund.  2) the form of women’s participation in the empowerment process trought the village fund in Tammejarra Village, namely; a) Building commitment, b) Organizing, c) Need assessment, d) Planing activities, e) Implementation, and f) evaluating.